2020
DOI: 10.1002/ejic.202000644
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli‐Responsive Emission of Dinuclear Rhombic Copper(I) Iodide Complexes Having Triphenylarsine and N‐Heteroaromatic Co‐Ligands

Abstract: Copper(I) iodide complexes of triphenylarsine with a series of N‐heteroaromatic co‐ligands, i.e., pyridine, 2‐picoline, 2,6‐lutidine, and quinoline, were synthesized. The structures of the complexes were analyzed by X‐ray crystallography, which revealed that they adopted dinuclear rhombic structures. It was found that the arsenic atom effectively worked for forming shorter cuprophilic interaction when compared with the corresponding triphenylphosphine complex. The N‐heteroaromatic co‐ligand highly affected Cu–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…The Cu–Cu distances, being important for emission properties of the complexes, 7 were altered by the triazole-ligands structures from 2.827(2) Å ( 2 ) to 3.037(2) Å ( 3 ). Complexes with 4-pyridine coordinating group tend to show shorter Cu⋯Cu separation while those with 3 pyridine coordinating derivatives tend to show the longer Cu⋯Cu separation.…”
Section: Resultsmentioning
confidence: 99%
“…The Cu–Cu distances, being important for emission properties of the complexes, 7 were altered by the triazole-ligands structures from 2.827(2) Å ( 2 ) to 3.037(2) Å ( 3 ). Complexes with 4-pyridine coordinating group tend to show shorter Cu⋯Cu separation while those with 3 pyridine coordinating derivatives tend to show the longer Cu⋯Cu separation.…”
Section: Resultsmentioning
confidence: 99%
“…Stimuli-responsive luminescent materials, especially those with high-contrast luminescence colors that are reversibly convertible to each other, have received considerable interest for their potential applications in optical sensor, data recording, bioimaging, and security system. However, the dual- and multiple-stimuli-responsive systems, particularly those with multicolor luminescence, are quite limited relative to the single-stimulus responsive ones. Stimuli-responsive luminescent materials based on metal complexes have become a research hotspot in recent years due to their advantages of easy modification of organic compounds and stability of inorganic compounds. Most of them are the platinum-, gold-, silver-, and other precious-metal-based complexes. Some copper- and zinc-based complexes also show good stimuli-responsive luminescence properties. Cuprous complexes are attractive for developing low-cost stimuli-responsive luminescent materials because of their good luminescent properties and diverse structures and abundant Cu element. However, it remains a challenge to precisely design multi-stimuli-responsive cuprous-emissive complexes that are easily synthesized and exhibit switchable multicolor luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…80 There are a dearth of Cu− arsenido (or any anionic arsenic) bonds in the literature, 84−89 but the Cu−As bond distances in 7 range from 2.322(1) to 2.421(1) Å, which is in the range of Cu−As bonds. 90,91 We also analyzed the bonding in 6 and 7 with DFT and found that it was also essential to include dispersion corrections to the PBE functional in order to obtain an optimized structure in reasonable agreement with experiment, particularly for the Th−P bond lengths. This is illustrated in Figure S21 for 6, which shows the orientations of the three μ 2 -MesPH obtained from the experimental crystal structure (Figure S21, left), PBE (Figure S21, middle), and PBE-D3-BJ (Figure S21, right).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These can be compared to the sum of the covalent radii of Th and arsenic, which is 3.25 Å . There are a dearth of Cu–arsenido (or any anionic arsenic) bonds in the literature, but the Cu–As bond distances in 7 range from 2.322(1) to 2.421(1) Å, which is in the range of Cu–As bonds. , …”
Section: Resultsmentioning
confidence: 99%